Undergraduates' Understanding of Agricultural Impacts on Wildlife: A Case for Wildlife Conservation Education. Issue 1 (3rd March 2017) - Sharp, Ryan; Ahlers, Adam
Abstract : Core Ideas: Students' perceptions of agriculture's impact on wildlife populations differ from science‐based information. Academic major may influence students' perceptions of agriculture's impact on wildlife populations. Where students obtain their information influences perceptions of wildlife conservation. Agricultural production is considered one of the leading drivers of declines in wildlife populations, and educating future land managers about agriculture's threat to biodiversity is required to help restore and maintain wildlife populations. University students enrolled in agriculture‐based majors will likely be future leaders in the agricultural industry; however, we have a limited understanding of the knowledge and perceptions our future agricultural leaders toward contemporary wildlife‐conservation issues. College students from an agriculture program at a land‐grant university in the U.S. Midwest were given an online survey that assessed their understanding of wildlife conservation related issues, and how agriculture may contribute to habitat loss for wildlife. Sample respondents (90.7%) felt that habitat loss is a major contributor to wildlife population declines; however, there was a difference in department‐specific responses in the college of agriculture for the questions about agriculture's contribution to declines in wildlife populations. There was also a difference between students with previous coursework related to wildlife conservation and those that had not taken wildlife related courses ( F = 6.59, p = 0.01). The observed differences in this study revealed that those with majors related to natural resources management and previous exposure to wildlife related classes were more likely to understand the impact that agriculture has on wildlife conservation. For these reasons, we suggest that all students graduating from agriculture colleges be required to take at least one course pertaining to wildlife conservation.